Dinoflagellate cyst counts of drifting trap surveys and In-situ pumps collected during Meteor cruise M165 in August 2020 - Karin A F Zonneveld; Gerard J M Versteegh; Hendrik Grotheer (PANGAEA, 2022)
To extend the understanding of dinoflagellate cysts production, excystment and vertical/ lateral transport in the water column, upper water dinoflagellate cyst export production have been compared with cysts associations and concentrations in the subsurface nepheloid layer, bottom nepheloid layer and deeper water column during active upwelling off Cape Blanc (NW Africa) in August 2020. Export production was collected by two drifting trap surveys; one in an active upwelling cell for 4 days and the other in an offshore drifting upwelling filament for 2 days. Subsurface and bottom nepheloid layers as well as the deeper waters were sampled by in-situ pumps along two transects perpendicular to the shelf break. The dataset represents the count data on species level of organic-walled dinoflagellate cysts in drifting trap and in-situ pump collected samples as well as information about the sampling time, sampling volume and collection surface.